Fecal microbiota transplantation and replenishment of short-chain fatty acids protect against chronic cerebral hypoperfusion-induced colonic dysfunction by regulating gut microbiota, differentiation of Th17 cells, and mitochondrial energy metabolism - Su, Shao-Hua; Wu, Yi-Fang; Lin, Qi; Zhang, Lin; Wang, Da-Peng; Hai, Jian (Journal of neuroinflammation, 2022)
Little is known about the association between gut microbiota and intestinal injury under a state of chronic cerebral hypoperfusion (CCH). Here, the effects of gut microbiota and short-chain fatty acids (SCFAs), as important metabolic products, on intestinal function and potential mechanisms after CCH were investigated. Rats were subjected to bilateral common carotid artery occlusion (BCCAo) to induce CCH. The gut microbiota and metabolites of SCFAs were assessed by 16S rRNA sequencing and targeted metabolomics, respectively. Transcriptomic analysis of colon tissues was also conducted. Subsequently, potential molecular pathways and differentially expressed genes were verified by western blot, immunoprecipitation, and immunofluorescence analyses. Furthermore, the integrity of the colonic barrier was evaluated by hematoxylin and eosin and mucin 2 staining and expression levels of tight junction proteins. Besides, colonic inflammation was further assessed by flow cytometry and expression levels of inflammatory cytokines. In addition, colonic mitochondrial dysfunction was analyzed via membrane potential, reactive oxygen species, electron transport chain (ETC) activities, adenosine triphosphate content, and mitochondrial ultrastructure. CCH modified gut microbial composition and microbial metabolism of SCFAs, which may be associated with inhibition of mitochondrial ETC activities and oxidative phosphorylation, leading to dysregulation of mitochondrial energy metabolism. Furthermore, CCH induced differentiation of pathogenic Th17 cells, promoted the formation of complexes of interferon regulatory factor 4 and signal transducer and activator of transcription 3 (STAT3), and increased the phosphorylation of STAT3. This was associated with an impairment of colonic barrier function and chronic colonic inflammation. In contrast, FMT and SCFA replenishment ameliorated CCH-induced gut microbial dysbiosis by increasing the intestinal content of Ruminococcus_sp_N15_MGS_57 and modulating microbial metabolism of SCFAs by increasing acetic acid contents associated with an improvment of the balance between Tregs and Th17 cells, mitochondrial ETC activities, and oxidative phosphorylation to prevent colonic inflammation and dysregulation of mitochondrial energy metabolism. These findings indicate that FMT and SCFA replenishment present a promising therapeutic strategy against colonic dysfunction under a state of chronic cerebral ischemia.